Enhancing Basketball Performance through Dance Culture Application Modeling in Sports Science and Enterprise Contexts - Xiaolei LIU (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This paper explores the innovative integration of dance culture application modeling within the context of basketball, with a dual emphasis on sports science and enterprise applications. The convergence of dance and basketball offers a unique opportunity to enhance player performance, promote physical conditioning, and facilitate dynamic teamwork. In sports science, the infusion of dance-inspired exercises and routines into basketball training regimens has proven instrumental in enhancing athletes' agility, coordination, and balance. These fundamental attributes are essential for basketball players to excel in dribbling, shooting, and defensive maneuvers. Furthermore, dance culture application modeling contributes to optimal physical conditioning, bolstering cardiovascular endurance and muscular strength, and basketball players maintain peak performance levels throughout the game. Beyond the court, the marriage of dance and basketball presents exciting prospects for enterprises within the sports industry. Team cohesion and motivation are vital for success, and dance culture modeling fosters teamwork, synchronization, and camaraderie among players. Such attributes translate into better on-court performance and contribute to a more marketable and engaging sports product. This approach can be a potent tool for branding, fan engagement, and marketing initiatives within the basketball ecosystem. Additionally, dance culture application modeling can play a pivotal role in injury prevention and rehabilitation, safeguarding players' physical well-being and prolonging their careers. It also offers a refreshing avenue for player wellness during off-seasons and recovery periods. This abstract showcases the promising intersection of dance culture application modeling with basketball, transcending conventional training methodologies. Through its amalgamation of sports science and enterprise applications, it not only elevates player performance but also enhances the appeal and viability of basketball as a dynamic and marketable sport.